Possibilities for authentication of the interaction parties based on recurrent sequences - Яремчук, Юрій Євгенович (Ukrainian Information Security Research Journal, 2014)
To date, for solving the integrity provision problem of broad utilization, we received protocols of authentication and digital signature. Amongst them, protocols of the parties to interaction hold an important place, when a checkup of the fact that the interacting party is the self-identified party, is conducted by one party. The existing authentication methods are based mainly on operations of exponentiation, requiring implementation of complex calculations, affecting the speed of the method at the stage of its practical implementation. We consider a possibility of creating an authentication method of the interaction parties based on the mathematical apparatus of recurrent sequences, based on the proportions in which the initial elements are associated with the coefficients. We have worked out a protocol implementing the method. The proposed method, compared with the known analogues, allowed to increase the cryptographic reliability of the authentication process, and the ability to change the reliability of the method depending on the sequence order. The presented developments made it possible to expand the use of authentication methods, especially in protection systems with high level of secrecy.